THE EFFECT OF LIQUIDITY AND SOLVENCY RATIOS ON PROFITABILITY AT PT INDOCEMENT TUNGGAL PRAKARSA TBK PERIOD 2011-2019 - Nurwita Nurwita; Putri Nilam Kencana; Lisdawati Lisdawati (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
The existence of the Industrial Revolution 4.0 era where the speed of information on technology is very much needed, especially to increase the profitability of a company, it is very necessary for the sustainability of the company, especially manufacturing companies that are engaged in creating products and then selling them to get the profitability of the company. Profit is also an indicator to measure the company's performance in managing financial management that is good, efficient, and effective. The purpose of the study is to find out whether there is a partial and simultaneous influence between the Independent variable and the dependent variable, namely Liquidity which is proxied by the Current Ratio (CR) with Variable Profitability is proxied by Return On Assets (ROA), Solvency variables are proxied by Debt to Assets Ratio (DAR) to Return On Assets (ROA) and to determine whether there is a simultaneous or joint effect on all dependent variables, namely Current Ratio (CR), Debt to Assets Ratio (DAR), Against Return On Assets (ROA). The population taken in this research is all the financial statements of PT Indocement Tunggal Prakarsa which are listed on the Indocement website and the sample studied is the Balance Sheet and Income Statement from PT Indocement Tunggal Prakarsa which is listed on the Indocement website. namely by collecting secondary data using a series of many tests, namely there is a classic assumption test (normality test, multicollinearity, heteroscedasticity, and autocorrelation), Multiple Regression Analysis Test, Coefficient of Determination Test, namely Adjusted R square, hypothesis test, namely there is a partial test and Simultaneous Test, and. The results of this study prove that the Current Ratio to Return on Assets is said to have a significant effect, and also the joint test of the Current Ratio and Debt to Assets Ratio variables has a significant effect on Return on Assets. But it is necessary to pay attention to the Debt to Assets Ratio variable (DAR) has no significant effect on Return on Assets.